(untitled) (Research, Society and Development, 2021)
Radical questions about the ideas linked to the notion of development, such as, growth, progress, market reform, extractivism, excessive increase in individual material consumption, etc., converge to alternative developments or alternatives to the idea of development itself. That said, this article discussed the differences between the concepts of ethnodevelopment and indigenous buen vivir in its interface with public policy through a conventional literature review. The results show that the idea of development has been transformed from modernization and economic growth to more critical or negative perspectives of the capitalist development paradigm. Ethnodevelopment, while focusing on the ethnic, historical and cultural issues in development processes, still does so for the purpose of economic efficiency. Buen vivir, on the other hand, seeks fullness and balance between peoples, nature and metaphysics, which puts it as an alternative to development, since it is not supported by Judaic-Christian, anthropocentric and rational-scientific logic. It is concluded that ethnodevelopment, from the indigenous perspective, seems to be less interesting as a development project and that buen vivir, although it has been constitutionally recognized in Bolivia and Ecuador, has always been in conflict due to capitalist colonization in ways of thinking about time, space, economics, social relations, nature, society and, therefore, public policy.